Determination of PCB Levels Indoor and Outdoor Dust Samples of Primary Schools in Düzce - Aslı TEKLİ; Seda Aslan Kılavuz; Zehra Bozkurt (Doğal Afetler ve Çevre Dergisi)
Düzce province, where industry, traffic and residential areas are intertwined, is developing rapidly and therefore environmental pollution is intensely felt in the region. Air pollutants from emission sources cannot be dispersed due to the geographical location of the province and pose important health risks. In this study, dust samples were collected at different locations in order to explain the regional pollution distribution and various emission sources. Because children are more sensitive to air pollutants, indoor and outdoor environments of primary schools were selected for sampling. PCB levels were determined in dust samples collected from indoor and outdoor environments of the primary schools in Düzce. PCB analyses were performed by using the Gas chromatograph/Mass Spectrometer (GC/MS) instrument. In the obtained results, outdoor ΣPCB concentrations were between 0.737 and 22.307 ng/gr, with an average of 3,626 ng/gr. Indoor ΣPCB concentrations were between 17.17 and 294.22 ng/gr, with an average of 66.89 ng/gr. High ∑PCB concentrations in indoor samples show that the contribution of indoor sources and the effect of accumulation in indoor environments by transport from the outdoor environments is greater. In the evaluation made according to outdoor sources, the highest concentrations were obtained mostly at points close to the industrial area. The lowest concentrations were measured at rural sampling points.